Interaction of hydrogen sulfide and estrogen on the proliferation of vascular smooth muscle cells. - Hongzhu Li (Public Library of Science (PLoS), 2012)
Hydrogen sulfide (H(2)S) can be endogenously generated from cystathionine gamma-lyase (CSE) in cardiovascular system, offering a cardiovascular protection. It is also known that the lower risk of cardiovascular diseases in female is partially attributed to the protective effect of estrogen. The current study explores the interaction of H(2)S and estrogen on smooth muscle cell (SMC) growth. In the present study, we found that the proliferation of cultured vascular SMCs isolated from wild-type mice (WT-SMCs) was inhibited, but that from CSE gene knockout mice (CSE-KO-SMCs) increased, by estrogen treatments. The expression of estrogen receptor α (ERα), but not ERβ, was significantly decreased in CSE-KO-SMCs compared with that in WT-SMCs. Exogenously applied H(2)S markedly increased ERα but not ERβ expression. In addition, the inhibition of ER activation and knockdown of ERα expression in WT-SMCs or the overexpression of ERα in CSE-KO-SMCs reversed the respective effects of estrogen on cell proliferation. The expression of cyclin D1 was reduced in WT-SMCs but increased in CSE-KO-SMCs after estrogen treatments, which was reversed by knockdown of ERα in WT-SMCs or overexpression of ERα in CSE-KO-SMCs, respectively. The overexpression of cyclin D1 in WT-SMCs or knockdown of cyclin D1 expression in CSE-KO-SMCs reversed the effects of estrogen on cell proliferation. These results suggest that H(2)S mediates estrogen-inhibited proliferation of SMCs via selective activation of ERα/cyclin D1 pathways.